Survival in early lung cancer patients treated with high dose radiotherapy is independent of pathological confirmation. Issue 2 (7th January 2019) - Zehentmayr, Franz; Sprenger, Martin; Rettenbacher, Lukas; Wass, Romana; Porsch, Peter; Fastner, Gerd; Pirich, Christian; Studnicka, Michael; Sedlmayer, Felix
Abstract : Background: Approximately 15% of lung cancer patients are diagnosed in early stages. Microscopic proof of disease cannot always be obtained because of comorbidity or reluctance to undergo invasive diagnostic procedures. In the current study, survival data of patients with and without pathology are compared. Methods: One hundred and sixty three patients with NSCLC I–IIb (T3 N0) treated between 2002 and 2016 were eligible: 123 (75%) had pathological confirmation of disease, whereas 40 (25%) did not. In accordance with international guidelines, both groups received radiotherapy. Comorbidity was assessed with the Charlson Comorbidity Index (CCI). Results: The median follow‐up was 28.6 months (range: 0.3–162): 66 (40%) patients are still alive, while 97 (59%) patients died: 48 (29%) cancer‐related deaths and 49 (30%) from causes other than cancer. Median overall survival (OS) in patients without pathological confirmation was 58.6 months (range: 0.5–162), which did not differ from those with microscopic proof of disease (39.4 months, range: 0.3–147.5; logrank P = 0.481). Median cancer‐specific survival (CSS) also did not differ at 113.4 months (range: 0.5–162) in the non‐confirmation group (logrank P = 0.763) versus 51.5 months (range: 3.7–129.5) in patients with pathology. In Cox regression, a CCI of ≥ 3 was associated with poor OS (hazard ratio 2.0; range 1.2–3.4; P = 0.010) and CSS (hazard ratio 2.0; 1.0–4.0; P = 0.043). Conclusion: OS and CSS in early lung cancer patients depend on comorbidity rather than on pathological confirmation of disease.